Epidemiological and entomological studies of a malaria outbreak among French armed forces deployed at illegal gold mining sites reveal new aspects of the disease's transmission in French Guiana. (December 2016) - Santi, Vincent; Girod, Romain; Mura, Marie; Dia, Aissata; Briolant, Sébastien; Djossou, Félix; Dusfour, Isabelle; Mendibil, Alexandre; Simon, Fabrice; Deparis, Xavier; Pagès, Frédéric
Abstract Background In December 2010, aPlasmodium vivax malaria outbreak occurred among French forces involved in a mission to control illegal gold mining in French Guiana. The findings of epidemiological and entomological investigations conducted after this outbreak are presented here. Methods Data related to malaria cases reported to the French armed forces epidemiological surveillance system were collected during the epidemic period from December 2010 to April 2011. A retrospective cohort study was conducted to identify presumed contamination sites.Anopheles mosquitoes were sampled at the identified sites using Mosquito Magnet and CDC light traps. Specimens were identified morphologically and confirmed using molecular methods (sequencing of ITS2 gene and/or barcoding).Anopheles infections withPlasmodium falciparum andP. vivax were tested by both enzyme-linked immunosorbent assay and real-time PCR. Results Seventy-twoP. vivax malaria cases were reported (three were mixedP. falciparum /P. vivax infections), leading to a global attack rate of 26.5 % (72/272). Lack of compliance with vector control measures and doxycycline chemoprophylaxis was reported by patients. Two illegal gold mining sites located in remote areas in the primary forest were identified as places of contamination. In all, 595Anopheles females were caught and 528 specimens were formally identified: 305Anopheles darlingi, 145Anopheles nuneztovari s.l., 63Anopheles marajoara and 15Anopheles triannulatus s.l. ThreeAn. darlingi were infected byP. falciparum (infection rate: 1.1 %) and fourAn. marajoara byP. vivax (infection rate: 6.4 %). Discussion The main drivers of the outbreak were the lack of adherence by military personnel to malaria prevention measures and the high level of malaria transmission at illegal gold mining sites.Anopheles marajoara was clearly implicated in malaria transmission for the first time in French Guiana. The high infection rates observed confirm that illegal gold mining sites must be considered as high level malaria transmission areas in the territory. Conclusions Illegal gold mining activities are challenging the control of malaria in French Guiana. Collaboration with neighbouring countries is necessary to take into account mobile populations such as gold miners. Malaria control strategies in the French armed forces must be adapted toP. vivax malaria and sylvaticAnopheles species.